Pengaruh Model Leadership dan Gaya Komunikasi Organisasi Terhadap Kinerja Karyawan di RS Metro M.Toha Tangerang - Wibisono, Aryo; Yaniawati, Poppy; Restiani Widjaja, Yani (ManBiz: Journal of Management and Business, 2025)
Organizations need to treat human resources as a crucial production factor to enhance employee performance through cooperation and a supportive work environment. At Metro Hospitals M Toha, high absenteeism and low productivity are challenges that necessitate an effective organizational communication model to improve performance. This study aims to analyze the influence of leadership models and communication styles on employee performance, particularly in the inpatient ward, to enhance management practices in healthcare. The research at Metro Hospitals M. Toha in Tangerang uses a mixed-method approach to integrate qualitative and quantitative data, aiming to analyze the impact of leadership styles and organizational communication on employee performance through surveys, interviews, observations, and documentation from February to July 2024. The study concludes that the transformational leadership style at Metro M. Toha Hospital enhances employee performance, with performance declining if this style diminishes. Two-way communication styles, such as the Equalitarian, are also positively related to performance. Transparency and consistency in communication reduce misunderstandings and enhance motivation. The synergistic relationship between transformational leadership and effective communication boosts productivity, especially in inpatient wards. It is recommended to enhance this leadership style through participative approaches and communication training, as well as building a collaborative organizational culture